Novel SNPs in DGAT1 gene and their association with milk traits in Murrah buffaloes - Sulabh, Sourabh; Verma, Archana; Gupta, I D; Kumar, Bharat (Indian Journal of Dairy Science, 2018)
Diacylglycerol O-acyltransferase1Â (DGAT1) gene is one of the candidate genes for milk production traits. The gene is located on BBU15, spans over 8717 bp and encoded by 489 amino acids. Present study was carried out to identify SNPs in DGAT1 gene and their association with milk yield and composition traits. Genomic DNA was extracted from whole blood samples of 110 lactating Murrah buffaloes. Targeted region of exon 7-9 was amplified to get 412 bp PCR product. A total of 5 SNPs: g.T6880A and g.A6915G in intron 7, g.A7013G in exon 8, g.G7079C in intron 8 and g.G7134C in exon 9 were identified by direct DNA sequencing and Clustal W alignment. All the animals included in present study had fixed DGAT1K allele. However, g.G7013C and g.C7134G were non-synonymous SNPs leading to amino acid substitution p.Thr249Ala and p.Leu266Val, respectively. SIFT software predicted p.Thr249Ala to affect the protein function. Statistical analyses were performed for association between identified SNPs of DGAT1 targeted region and first lactation 305 days milk yield, fat percentage and fat yield. SNP g.A7013G was significantly (Pâ€‰